Pengaruh Pembatasan Aktivitas Ekonomi dan Perkembangan Investasi E-Commerce terhadap Minat Berinvestasi yang Dimoderasi oleh Tax Incentives di Era Covid 19 - Sitorus, Riris Rotua (Media Akuntansi Perpajakan, 2021)
In making good investment decisions, there are 3 methods as an option, the first is managing your own investment, using advisory services and the third is using robo advisor. In this study, it is explained that the development of digital technology is able to provide online information that can influence decisions about various information about a project or product when making an investment decision. In general, the basic objective of investing is to build wealth. However, after the announcement of a positive patient case for Covid-19 on March 2, 2020, various strategies to deal with covid-19 were carried out by the Government of Indonesia, such as contact tracing, rapid testing, and adequate treatment. With the doubts experienced by the central government, it caused delays in decision-making that made Covid-19 spread so fast. With the acceleration of the spread of Covid-19, followed by travel bans, border closings and quarantine measures, it has a direct impact on people's incomes, especially for informal workers and casual workers. On the other hand, the government has also relaxed income tax in articles 21, 22 and 25 as well as SPT which are the most effective and appropriate way to overcome the impact of Indonesia's economy in the face of the Covid-19 outbreak.Keywords: economic activity restrictions, e-commerce investment, investment interest, tax incentives in the covid-19 era